2014
DOI: 10.1111/gean.12027
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Externalities in Innovation, Trade, and Regional Economic Growth

Abstract: We build on Grossman and Helpman (1991), Rivera‐Batiz and Romer (1991), Acemoglu (2009, pp. 678–80), and Batabyal and Nijkamp (2013b) and analyze the interactions between positive and negative externalities in innovation and trade for economic growth in a region when this region is part of an aggregate economy consisting of two regions. In both regions, consumers have constant relative risk aversion preferences; there is human capital use, and there are three kinds of manufacturing activities involving the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In view of the above, after consulting the relevant literature, this paper found that the two ratios are closely related to knowledge elements and absorptive capacity. Knowledge is an important factor in innovation development, and its spillover has a significant effect on sustainable economic development [1]. Absorptive capacity also plays a positive role in this process [2].…”
mentioning
confidence: 99%
“…In view of the above, after consulting the relevant literature, this paper found that the two ratios are closely related to knowledge elements and absorptive capacity. Knowledge is an important factor in innovation development, and its spillover has a significant effect on sustainable economic development [1]. Absorptive capacity also plays a positive role in this process [2].…”
mentioning
confidence: 99%
“…Therefore, to compensate for the incurred costs, it is necessary to establish property rights. The lack of clearly established rights can lead to uncontrolled spatial management processes and the lack of awareness of generating externalities for other users (Batabyal and Nijkamp 2014;Baumol and Oates, 1993). Establishing and granting ownership rights to entities functioning within the framework of adopted principles and regulations in force will prevent the internalization of external costs.…”
Section: Externalities and Their Classification A Theoretical Backgroundmentioning
confidence: 99%
“…To this end, the wealth gap in America has steadily increased over the last 50 years, and recent polling data indicates that 61% of Americans say there is too much inequality (Schaeffer 2020). Further, while economic growth tends to be viewed as a positive, its benefits are not always equally distributed and can lead to displacement and competition over resources (Batabyal and Nijkamp 2014). On one hand, the U.S. has shifted towards a service-based economy and a strong technology sector, and away from more traditional industries, such as manufacturing and agriculture.…”
Section: Economic Inequality and Changementioning
confidence: 99%